1981
DOI: 10.1111/j.1476-5381.1981.tb08744.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender on Development and Diurnal Rhythm of Prostaglandin Receptors in Rat Aorta

Abstract: 1 The prostaglandin endoperoxide H2 analogue, U-46619 (15-hydroxy-11, 9-epoxymethanoprosta-5Z, 13E-enoic acid), was used to determine the effect of gender on the isotonic contractile response of the superfused rat aorta preparation over a 24 h period and at 10 and 16 weeks of age. 2 The maximal responses of the male aortae were 20 ± 3% and 36 ± 4% (P< 0.001) greater than the female at 10 and 16 weeks, respectively. Similarly, sensitivity of the male aorta to the PGH2 analogue increased with age. 3 The male but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
(9 reference statements)
3
0
0
Order By: Relevance
“…This study provides evidence that testosterone treatment enhances the vasoconstrictor response to TXA2 in the coronary circulation and also produce a diathesis for induction of coronary artery vasospasm. These observations are consistent with the previous studies that demonstrated an enhanced responsiveness of male aortas compared to females to U46619 [ 15]. In addition it has also been demonstrated that treatment of rabbits with testosterone enhanced the response of the isolated aorta to U46619 [16].…”
Section: Discussionsupporting
confidence: 93%
“…This study provides evidence that testosterone treatment enhances the vasoconstrictor response to TXA2 in the coronary circulation and also produce a diathesis for induction of coronary artery vasospasm. These observations are consistent with the previous studies that demonstrated an enhanced responsiveness of male aortas compared to females to U46619 [ 15]. In addition it has also been demonstrated that treatment of rabbits with testosterone enhanced the response of the isolated aorta to U46619 [16].…”
Section: Discussionsupporting
confidence: 93%
“…In a megakaryocyte-like cell line, TXA2Rs undergo internalization and degradation during the process of desensitization [35,36]. This finding is consistent with the previous observations that male rabbit or rat aortae were more sensitive and exhibited a greater maximum response to U-46619 than female aortae [80]. Preliminary studies showed that testosterone increased receptor density and receptor responsiveness to TXA2 in cultured rat aortic smooth muscle cells and HEL cells, presumably by induction of receptor gene expression since cycloheximide and actinomycin D blocked the process [108][109][110].…”
Section: Regulation Of Thromboxane a 2 Receptorssupporting
confidence: 91%
“…Preliminary studies showed that testosterone increased receptor density and receptor responsiveness to TXA 2 in cultured rat aortic smooth muscle cells and HEL cells, presumably by induction of receptor gene expression since cycloheximide and actinomycin D blocked the process [108][109][110]. This finding is consistent with the previous observations that male rabbit or rat aortae were more sensitive and exhibited a greater maximum response to U-46619 than female aortae [80]. In fact, rats treated with testosterone have increased TXA 2 R responses to TXA 2 mimetics.…”
Section: Regulation Of Thromboxane a 2 Receptorssupporting
confidence: 83%